Knowledge, attitude and practice of rehabilitation management of the caregivers of pediatric patients with hemiplegia - Ya Guo; Xiaoli Li; Gongwei Jia; Jiahong Zhan; Zhongyu He; Guangshen Yuan; Chunyan Liu; Yuanyuan Lai (Scientific Reports)
Abstract This study aimed to assess the knowledge, attitude, and practice (KAP) of caregivers managing rehabilitation for pediatric hemiplegia patients. Conducted at our hospital from January 25 to July 20, 2024, self-developed questionnaires were used to evaluate KAP scores among caregivers and compare demographic factors. Spearman correlation analysis explored relationships between variables, and structural equation modeling (SEM) examined direct effects. A total of 547 valid questionnaires were analyzed, with 71.48% female respondents and 90.86% parents of pediatric patients. The mean KAP scores were 6.63 ± 0.66 (range: 0–7), 23.50 ± 2.26 (range: 6–30), and 42.63 ± 5.32 (range: 10–50), respectively. Spearman correlation analysis revealed positive correlations between knowledge and attitude (r = 0.0889, P = 0.0377), and between attitude and practice (r = 0.5550, P < 0.001). SEM confirmed direct associations between monthly income and knowledge (path coefficient = 0.09, P = 0.002), knowledge and attitude (path coefficient = 0.28, P = 0.048), and education level and attitude (path coefficient = 0.46, P = 0.001). Additionally, attitude (path coefficient = 1.27, P < 0.001) and the dominant hand of pediatric patients (path coefficient = 1.34, P < 0.001) were directly associated with practice. Knowledge (path coefficient = 0.35, P = 0.049) and education level (path coefficient = 0.58, P = 0.001) were indirectly linked to practice. Caregivers of pediatric patients with hemiplegia displayed adequate knowledge, positive attitudes, and proactive practices in rehabilitation management. Educational interventions and support programs are suggested, especially for caregivers with lower income and education levels.